Heat Transfer Characteristics and Pressure Drop of U-type Channel in Vacuum Distillation Process for Titanium Sponge - Yang, Kangquan; Zhang, Chengqi; Yuan, Hui; Wu, Fuzhong (Frontiers in Energy Research, 2022)
Blockage of the U-type channel exacerbates the intermittency of production, and clarifying the channel heat transfer characteristics and pressure drop is an effective way to address this problem. The channel heat transfer and flow characteristics of the fluid in the channel are experimentally investigated in this study. According to the experiments, the heat transfer coefficient is between 59.95 and 200.29 W/m2⋅K and increases with the flow velocity and fluid temperature. Because the pressure drop is usually accompanied by a change in the energy loss of the fluid, the energy loss is evaluated experimentally. The results demonstrate that the friction loss in the straight tube section accounts for 80% of the energy loss. A bent tube of 90° is recommended instead of a right-angle tube to reduce the pressure drop. A dimensionless relation regarding the Nusselt number is presented to predict the heat transfer characteristics.